PENGARUH CITRA MEREK, KUALITAS LAYANAN DAN HARGA TERHADAP PREFERENSI KONSUMEN DALAM MENGGUNAKAN APLIKASI GOJEK - Permana, Septian Davis; Dwiridotjahjono, Jojok (STKIP Persada Khatulistiwa Sintang, 2023)
The emergence of several technological developments in transportation such as Uber, Grab, GoJek provide easy access to certain places and can be reached very quickly with adequate vehicles. This research aims to examine the influence of brand image, service quality and price on consumer preferences in using the Gojek application among students of the Business Administration study program at FISIP UPN